Distal Arterialized Venous Supercharging Improves Perfusion and Survival in an Extended Dorsal Three-Perforasome Perforator Flap Rat Model. Issue 6 (25th May 2021) - Wu, Hongqiang; Zhang, Chenxi; Chen, Zhengtai; Lou, Junsheng; Ding, Jian; Wang, Long; Xie, Chenglong; Gao, Weiyang; Lin, Damu
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Perforator flaps are commonly applied for a variety of skin defects. Many strategies (e.g., hyperbaric oxygen and preconditioning) have been investigated to improve flap survival, but a postoperative 2.03 to 18.2 percent flap necrosis frequency remains a major complication. The authors hypothesized that a distal arterialized venous supercharged (DAVS) flap procedure might improve perfusion and survival in an extended three-perforasome perforator flap rat model and rescue flap ischemia intraoperatively. Methods: One hundred twenty male Sprague-Dawley rats (200 to 300 g) were divided into the thoracodorsal artery (TDA) flap group and the DAVS flap group ( n = 60 per group). An approximately 11 × 2.5-cm 2 flap based on the TDA perforasome was designed in the TDA flap. A DAVS flap was designed based on the TDA flap and supercharged by anastomosing the rat caudal artery with the deep circumflex iliac vein. At postoperative times 1, 3, 6, and 12 hours and 1, 3, 5, and 7 days, perfusion and angiography were compared. On day 7, flap viability and angiogenesis were assessed using histology and Western blotting. Results: The DAVS flap showed a higher survival rate compared with the TDA flap (100 percent versus 81.93 ± 5.38 percent; p < 0.001). All blood flow ratios of deep circumflex iliac artery to TDA perforasome and of choke zone II to choke zone I were higher in the DAVS flap (all p < 0.05). Angiography qualitatively revealed that choke vessels in choke zone II dilated earlier and extensively in the DAVS flap group. CD34 + vessels (68.66 ± 12.53/mm 2 versus 36.82 ± 8.99/mm 2 ; p < 0.001) and vascular endothelial growth factor protein level (0.22 ± 0.03 versus 0.11 ± 0.03; p < 0.001) were significantly increased in the DAVS flap group. Conclusions: The DAVS procedure improves three-perforasome perforator flap survival and can be used for rescuing flap ischemia intraoperatively. Further study is needed before possible clinical adoption for reconstructive operations.